Биоиндикация загрязнения атмосферного воздуха химическими предприятиями - Рыжакова Н. К. Надежда Кирилловна; Борисенко А. Л. Алексей Леонидович; Рогова Н. С. Наталья Сергеевна; Меркулов В. Г. Виктор Георгиевич (2013, 2013)
Заглавие с экрана